2021
DOI: 10.21037/apm-21-1599
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating health-related quality of life in gastric cancer patients in Suzhou, China

Abstract: Background: Health-related quality of life (HRQOL) has become an important part of the evaluation of clinical efficacy and prognosis in gastric cancer. This study aimed to assess the HRQOL of patients with gastric cancer using the a five-level EuroQol five-dimensional questionnaire (EQ-5D-5L) and explore the factors influencing patients' perceived quality of life. For those significant factors, we can take appropriate measures to intervene to extend patient survival and improve the quality of life. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The dimension where patients were most likely to report problems was pain/discomfort in all groups in this study, followed by anxiety/depression. This finding was supported by data showing that pain/discomfort was also the domain with the highest proportion of reporting problems, whereas anxiety/depression was the second [ 26 , 27 ]. Approximately, 40% of cancer survivors experience pain due to cancer treatment and complications [ 33 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The dimension where patients were most likely to report problems was pain/discomfort in all groups in this study, followed by anxiety/depression. This finding was supported by data showing that pain/discomfort was also the domain with the highest proportion of reporting problems, whereas anxiety/depression was the second [ 26 , 27 ]. Approximately, 40% of cancer survivors experience pain due to cancer treatment and complications [ 33 ].…”
Section: Discussionmentioning
confidence: 56%
“…Our findings confirmed previous research that demonstrated a decline in the quality of life decreased as GC progressed [ 25 , 26 ]. However, another study found that patients with stage I had the lowest utility value [ 27 ]. This could be because most of the gastric cancer patients at stage I in the previous study were treated with surgery, and there was a brief period between surgery and that research.…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate Tobit regression model was employed to assess the association between EQ-5D utility scores and its The Tobit model was chosen because of a common ceiling effect in the EQ-5D instruments, as a large number of patients report the highest health state, leading to some utility scores being censored at 1.0. 34,35 Therefore, when it comes to censored data, the use of Tobit regression model is advised. 36 Data were analyzed using STATA version 15.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the disease and its therapies on patients’ physical, social, and emotional health, measured through HRQL, may be accurately assessed in patients with upper gastroenterological problems, which is useful for therapeutic decision making. Three key domains—general function, well-being perception, and subjective symptoms—are used to assess the HRQL of patients with upper gastrointestinal illnesses [ 107 , 108 ]. Patients’ viewpoint on the outcome and impact of the therapy as well as the experiences of patients suffering from gastric and esophageal cancer, which are characterized by a poor prognosis, are imprinted in HRQL [ 76 , 109 ].…”
Section: Discussionmentioning
confidence: 99%